2014
DOI: 10.1021/ja502113d
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Nuclear Polarization NMR Enables the Analysis of Sn-Beta Zeolite Prepared with Natural Abundance 119Sn Precursors

Abstract: The catalytic activity of tin-containing zeolites, such as Sn-Beta, is critically dependent on the successful incorporation of the tin metal center into the zeolite framework. However, synchrotron-based techniques or solid-state nuclear magnetic resonance (ssNMR) of samples enriched with 119Sn isotopes are the only reliable methods to verify framework incorporation. This work demonstrates, for the first time, the use of dynamic nuclear polarization (DNP) NMR for characterizing zeolites containing ∼2 wt % of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
169
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(179 citation statements)
references
References 46 publications
6
169
2
2
Order By: Relevance
“…Hwang et al (92) also showed with 19 F- 119 Sn CP MAS NMR that even after calcination, Sn-Beta samples may contain some fluorine that associates with hydrated Sn sites. Recently, hyperpolarization techniques, such as DNP, have been successfully applied to characterize natural abundance 119 SnBeta samples (93). This technique allows transfer of the polarization from an exogenous biradical containing unpaired electrons to the Sn sites in the sample through the assistance of microwave radiation and a glassing agent.…”
Section: Direct Detection Of the Metal Centermentioning
confidence: 99%
“…Hwang et al (92) also showed with 19 F- 119 Sn CP MAS NMR that even after calcination, Sn-Beta samples may contain some fluorine that associates with hydrated Sn sites. Recently, hyperpolarization techniques, such as DNP, have been successfully applied to characterize natural abundance 119 SnBeta samples (93). This technique allows transfer of the polarization from an exogenous biradical containing unpaired electrons to the Sn sites in the sample through the assistance of microwave radiation and a glassing agent.…”
Section: Direct Detection Of the Metal Centermentioning
confidence: 99%
“…[17][18][19][20] Although recent experimental studies evidence a considerable heterogeneity of Sn speciation in different Sn-Beta zeolites, [21][22][23] there is an agreement that the active sites are partially hydrolyzed lattice Sn sites bearing an extraframework OH ligand (open Sn sites). [24][25][26][27][28] DFT calculations show that the cooperative action between the strong Lewis acid sites and neighboring protondonating groups results in a favorable reaction path for the hydride shift reaction, which is the key step in sugar isomerization. 20,[29][30][31][32][33][34] Although theory predicts that confinement should have only minor influence on the intrinsic reactivity of the cooperative reaction centers, zeolite topology will strongly affect the adsorption and diffusion of carbohydrates in the micropores.…”
Section: Introductionmentioning
confidence: 99%
“…However, the other two chemical shifts (at -670 and -728 ppm) are ascribed to hydrated, Sn(IV) species in Td sites (closed and/or open sites). 11,22,23 There are, however, somewhat broader features in 6%CoSn-700C sample (Fig. 3A, curve b) suggesting also the presence of multiple Sn environments in this sample.…”
Section: Sn Mas Nmrmentioning
confidence: 83%
“…119 Sn MAS-NMR has been used extensively for probing the nature of Sn species in zeolites, [21][22][23] and these interpretations can be rationally extended for probing analogous species in AlPO-5. In Fig.…”
Section: Sn Mas Nmrmentioning
confidence: 99%